Epidemiology of continuous renal replacement therapy in Korea: Results from the National Health Insurance Service claims database from 2005 to 2016 - Sehoon Park; Soojin Lee; Hyung Ah Jo; Kyungdo Han; Yaerim Kim; Jung Nam An; Kwon Wook Joo; Chun Soo Lim; Yon Su Kim; Hyeongsu Kim; Dong Ki Kim (The Korean Society of Nephrology, 2018)
Background : Continuous renal replacement therapy (CRRT) is an important treatment modality for severe acute kidney injury. As such, the epidemiology of CRRT in Korea needs further investigation. Methods : We conducted a nationwide, population-based study analyzing the claims data from National Health Insurance Service of Korea. All index intensive care unit admission cases of CRRT in government-designated tertiary referral hospitals in Korea from 2005 to 2016 were included. Patients with a history of renal replacement therapy or who were under 20 years old were not considered. In addition to baseline and treatment characteristics, patient outcomes, including all-cause mortality and renal survival rates, were investigated. We stratified the study patients according to 3-year time periods and major regions of the nation. Results : We included 37,337 patients who received CRRT in Korea. The overall use of CRRT increased over time, and more than 80% of cases of acute renal replacement therapy were CRRT after 2014. Seoul was the region in which the majority of CRRT (45.0%) was performed. The clinical characteristics of CRRT patients were significantly different among time-intervals and regions. Both all-cause mortality and renal survival rates after CRRT were prominently improved in the recent time periods (P ＜ 0.001). Conclusion : CRRT is a widely used treatment strategy for severe acute kidney injury in Korea. The prognosis of CRRT patients has improved compared to the past. This epidemiological study of CRRT in Korea revealed notable trends with regard to time period and geographic region.